KM Maturity Assessment of Telecommunication Company in Indonesia using G-KMMM - Hanif Sudira; Putra Tresna Linge; Tsaqif Alfatan Nugraha; Damayanti Elisabeth; Sofian Lusa; Dana Indra Sensuse (Proceeding of International Conference on Science, Health, And Technology, 2021)
The knowledge that has a relationship with the organization directly or indirectly affects an organization's sustainability. For this reason, a company, at least to survive, must have a good knowledge management process. TLCO is one of the largest telecommunication companies engaged in information and communication technology (ICT) services and telecommunications networks in Indonesia. TLCO plans to transform into a digital telecommunication company to adapt to changes in the telecommunications industry, taking place very quickly. It is necessary to know the maturity level of Knowledge Management as one aspect that can be used as TLCO readiness to transform into a digital company. This study aims to assess the maturity level of knowledge management in TLCO using G-KMMM and provide recommendations related to knowledge management for improvement. Data collection used a questionnaire to several people within the directorate at TLCO. Based on the assessment conducted using the GKMMM model with questionnaire data, the maturity level of knowledge management in TLCO is at level 2 or awareness.